THE EFFECTIVENESS OF TEAM ASISTED INDIVIDUALIZATION IN TEACHING VOCABULARY VIEWED FROM STUDENTS’ MOTIVATION - Sulaiman Sulaiman (Jurnal Pendidikan Bahasa, 2015)
AbstractThis research reveals an experimental study about the effectiveness of Team Assisted Individualization in teaching vocabulary at a private university in Pontianak. The population of this research was the first semester students of university. The sample was two classes consisting of 60 students taken by using cluster random sampling. The data analysis was done by applying descriptive and inferential statistics (ANOVA and Tukey Test) to test the research hypothesis.Based on the results of the analysis, the findings of this research are: (1) the students who were taught by using Team Assisted Individualization hadbetter vocabulary mastery that those who were taught  with Peer tutoring. In other words,  the use of Team Assisted Individualization was more effective than Peer Tutoring in teaching Vocabulary; (2) the students with high motivation had better vocabulary mastery than those with low motivation; and (3) there was interaction between teaching method and motivation toward students’ vocabulary mastery.Based on research findings, it can be concluded that Team Assisted Individualization is an effective teaching method to teach vocabulary for the first semester students of  university in Pontianak. The effectiveness of the method is influenced by the students’ level of motivation. Keywords: Team Assisted Individualization, Peer Tutoring Method, vocabulary , motivation.